Preparing Graduates for Employment. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2005)
Much has been said about graduate unemployment and the growing job mismatch of graduates and their qualifications. These issues are nothing new. What is worrying is the fact that at the heart of the conundrum lies the quality of the graduates themselves. This is one of the major findings of a study conducted by a team of researchers from Universiti Sains Malaysia recently.